2015
DOI: 10.18632/oncotarget.4017
|View full text |Cite
|
Sign up to set email alerts
|

Cynara scolymus affects malignant pleural mesothelioma by promoting apoptosis and restraining invasion

Abstract: Malignant pleural mesothelioma is a poorly treated neoplasia arising from the pleural mesothelial lining. Here we document that the leaf extract of Cynara scolymus exerts broad antitumoral effects both in vitro and in vivo on mesothelioma cell lines. We found that Cynara scolymus treatment affects strongly cell growth, migration and tumor engraftment of mesothelioma cell lines. Strikingly, dietary feeding with Cynara scolymus leaf extract reduces the growth of mesothelioma xenografted tumors similarly to pemet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 41 publications
1
38
0
2
Order By: Relevance
“…Cynaropicrin has anti-inflammatory, anti-tumor, TNF-α inhibitory, and antioxidant activities and hence it can also prevent the progression of HCC. Indeed, most natural agents do not induce a high level of toxicity and target multiple signaling pathways involved in cell growth, invasion, apoptosis, angiogenesis and metastasis (Pulito et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cynaropicrin has anti-inflammatory, anti-tumor, TNF-α inhibitory, and antioxidant activities and hence it can also prevent the progression of HCC. Indeed, most natural agents do not induce a high level of toxicity and target multiple signaling pathways involved in cell growth, invasion, apoptosis, angiogenesis and metastasis (Pulito et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Another clinical study recommended artichoke extract for treating hyperlipoproteinemia and, thus, prevention of atherosclerosis and coronary heart disease and showed that there were no drug-related adverse events indicating an excellent tolerability of artichoke extract (Englisch et al, 2000). Artichoke is a fundamental component of Mediterranean diet and is available globally in all markets (Pulito et al, 2015). (2) The compound is water-soluble and hence therapeutic injections can be formulated which will decrease the amount of dosage form and shorten the duration of therapy and thus reducing putative side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its putative anticancer effect has been studied, and some experimental data suggests that artichoke extracts could be applied as a nonconventional, adjuvant therapy for cancer chemoprevention and/or treatment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Аналогічні механізми та відповідний ефект виявлені при хронічному введенні екстракту у низьких дозах щодо клітин раку молочної зало-зи. Також ЕА виказував протипухлинний ефект in vitro та in vivo на культурах тканин та у тва-рин зі злоякісною плевральною мезотеліомою [43]. Крім цього, відомі антиапоптотичні вла-стивості ЕА за умов пошкодження ДНК, у тому числі алкілюючими агентами оваріальних клі-тин китайського хом'ячка [44].…”
unclassified
“…На думку дослід-ників, цей ефект пов'язаний з високим рівнем супероксиддисмутаз і лужної фосфатази. ЕА ре-комендується рядом дослідників як харчова до-бавка під час проведення протипухлинної хіміо-терапії [8,43,45].…”
unclassified